Is anxiety associated with hot flashes in women with breast cancer?. Issue 8 (August 2015) - Guimond, Anne-Josée; Massicotte, Elsa; Savard, Marie-Hélène; Charron-Drolet, Jade; Ruel, Sophie; Ivers, Hans; Savard, Josée
Abstract Objective Women with breast cancer are at higher risk for experiencing hot flashes (HFs), which is attributable, in large part, to systemic cancer treatments and their effects on estrogen levels. However, other factors, such as anxiety, could also play a role. This study aimed to assess the cross-sectional and temporal relationships between anxiety and HFs among women treated for breast cancer and to clarify the direction of these relationships. Methods Fifty-six women recently treated for breast cancer were assessed prospectively using a 14-day Hot Flashes and Anxiety Diary (HFAD). Anxiety and HFs were also assessed using the Hospital Anxiety and Depression Scale–anxiety subscale and the Menopause-Specific Quality of Life Questionnaire–vasomotor subscale. In addition, HFs were objectively recorded for a continuous 24-hour period using home-based sternal skin conductance. Results No cross-sectional relationship was found between anxiety and subjectively assessed HFs, or between anxiety and the frequency and intensity of objectively assessed HFs. However, a greater anxiety level on the HFAD was significantly associated with a shorter time to reach the HF peak, as assessed with sternal skin conductance (partial Spearman correlation coefficient rsp = −0.44). Moreover, greater anxiety predicted more severe self-reported HFs on the following night, both assessed with the HFAD (rsp = 0.13). Conversely, self-reported diurnal and nocturnal HFs on the HFAD did not predict next-day anxiety level. Conclusions This study reveals a significant relationship between anxiety and faster-developing objectively measured HFs. Furthermore, anxiety has been found to significantly predict subsequent increases in self-reported HFs, suggesting that strategies that target anxiety could potentially have a beneficial effect on HFs in women with breast cancer.